ROLE OF GENETIC FACTORS IN THE DEVELOPMENT OF METABOLICALLY ASSOCIATED FATTY LIVER DISEASE (LITERATURE REVIEW) - Elena Anatolievna Tkachuk; Igor Janovich Seminsky; Natalya M Kozlova; Sergey I Malov; Tatyana A Astakhova; Anastasia N Abramova; Raisa G Ubusheeva (Байкальский медицинский журнал)
Relevance. Liver diseases are a serious social problem. The study of the pathogenetic mechanisms of the development of these diseases, the search for treatment methods that can radically improve the patient’s condition and stop the development of the disease is very relevant and in demand.Aim: to conduct a literature review of currently known genetic factors in the etiology of non-alcoholic liver disease. Research results. The review presents the genetic aspects of the development of metabolically associated fatty liver disease (new name) or non-alcoholic fatty liver disease (common name). The leading syndromes accompanying the development of the disease are considered: asthenic syndrome, circadian rhythm disturbance syndrome ("circadian" syndrome), obstructive sleep apnea syndrome, cytolysis syndrome, insulin resistance syndrome, metabolic syndrome, pain syndrome, dyspeptic syndrome, irritable bowel syndrome, bacterial overgrowth syndrome growth, hepatomegaly and/or splenomegaly syndrome, fibrosis syndrome, polycystic ovary syndrome. The main comorbid conditions are covered: from the liver - hepatocellular carcinoma, cirrhosis of the liver, extrahepatic complications - obesity, type 2 diabetes mellitus, cardiovascular disorders - atherosclerosis, from the kidneys - chronic renal disease, etc. Data on genes affecting the development of diseases: PNPLA3, TM6SF2, MBOAT7, HSD17B13, GCKR, HFE, CP, INS, PPARG, CYP11A, AR, ENPP1, MTTP.Conclusion. Studying the etiological causes (genetic polymorphisms) of non-alcoholic fatty liver disease is the main task towards solving the problems of effective patient care.